Gut Microbiome and Space Travelers’ Health: State of the Art and Possible Pro/Prebiotic Strategies for Long-Term Space Missions - Turroni, Silvia; Magnani, Marciane; KC, Pukar; Lesnik, Philippe; Vidal, Hubert; Heer, Martina (Frontiers in Physiology, 2020)
The upcoming exploration missions will imply a much longer duration than any of the missions flown so far. In these missions, physiological adaptation to the new environment leads to changes in different body systems, such as the cardiovascular and musculoskeletal systems, metabolic and neurobehavioral health and immune function. To keep space travelers healthy on their trip to Moon, Mars and beyond and their return to Earth, a variety of countermeasures need to be provided to maintain body functionality. From research on ISS we know today, that for instance prescribing an adequate training regime for each individual with the devices available in the respective spacecraft is still a challenge. Nutrient supply is not yet optimal and must be optimized in exploration missions. Food intake is intrinsically linked to changes in the gut microbiome composition. Most of the microbes that inhabit our body supply ecosystem benefit to the host-microbe system, including production of important resources, bioconversion of nutrients, and protection against pathogenic microbes. The gut microbiome has also the ability to signal the host, regulating the processes of energy storage and appetite perception, and influencing immune and neurobehavioral function. The composition and functionality of the microbiome most likely changes during spaceflight. Supporting a healthy microbiome by respective measures in space travelers might maintain their health during the mission but also support rehabilitation when being back on Earth. In this review we are summarizing the changes in the gut microbiome observed in spaceflight and analog models, focusing particularly on the effects on metabolism, the musculoskeletal and immune systems and neurobehavioral disorders. Since space travelers are healthy volunteers, we focus on the potential of countermeasures based on pre- and probiotics supplements.